Are we all okay? Female empowerment in the graphic narrative of three Hispanic women authors (Encuentros, 2023)
With the growing popularity of graphic narratives comes the increasing participation of women in literary circles. This work focuses on the work of three authors of Hispanic culture, from different geographical areas, in order to examine their contribution to this hybrid literary field, which combines text and image: Poncho fue (2017) by Sole Otero, Estamos todas bien (2017) by Ana Penyas, and Cuarto oscuro (2018) by Lila Quintero Weaver. Although their works relate to different periods of the 20th century, they show a common denominator in individual and/or collective memory, which they recover to build their identities and process issues such as trauma, and racial or gender oppression. This analysis reveals how the combination of the written word and the graphic rendition empowers the authors and allows them to show the past in a different light than before and reclaim a modified vision of the present and the future.
Keywords: Women, Memory, Trauma, Empowerment, Graphic Narrative, Ethnic Discrimination.